2014
DOI: 10.1007/s11113-014-9339-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Security on Return Migration Among Latin American Elderly in the US

Abstract: International migration has long been considered the preserve of working-age adults. However, the rapid diversification of the elderly population calls for increased attention to the migration patterns of this group and its possible motivations. This study examines whether Latin American immigrants who are primary Social Security beneficiaries are more likely to return to their home countries during later life if they receive lower Social Security benefits. Using a regression discontinuity approach on restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Despite the heavy focus on employment- and income-related migration in the return migration literature ( e.g. Durand et al 1996; Stark, Hemelstein and Yegorov 1997; Vega 2015), results show that relatively few former US immigrants returned to Mexico for these reasons. Employment and wages may be the primary reasons that immigrants move to the USA but family relationships may become more important after they reach their initial financial goals.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the heavy focus on employment- and income-related migration in the return migration literature ( e.g. Durand et al 1996; Stark, Hemelstein and Yegorov 1997; Vega 2015), results show that relatively few former US immigrants returned to Mexico for these reasons. Employment and wages may be the primary reasons that immigrants move to the USA but family relationships may become more important after they reach their initial financial goals.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have suggested that social and familial ties may have an even greater influence than income in determining return migration (Massey 1987b; Vega 2015). For example, older Spanish and Italian immigrants in Switzerland listed the location of children as the most important factor in their retirement location decisions (Bolzman 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, older Mexicans have social and financial incentives for return migration, defined here as the act of returning to the country of origin, such as social support and land ownership (Massey 1987b), and reentry migration, which we define as the act of reentering the United States from Mexico, including proximity to children and grandchildren, and retirement benefits (Banks 2009). Despite these push and pull factors, research often treats international retirement migration as a singular occurrence and ignores the possibility of return to the home country and subsequent reentry back to the United States (e.g., Aguila and Zissimopoulos 2008; Casado-Díaz et al 2004; Sunil et al 2007; Vega 2015). By doing so, the current literature leaves unexamined the important implications that the timing and duration of migration spells have on micro- and macro-level outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a vibrant literature on the characteristics of entering migrants, there is far less information on migrants exiting the country. Studies document considerable migration among foreign-born primary social security beneficiaries (e.g., Turra & Elo, 2008;Vega, 2015) but do not examine emigration among immigrants who are ineligible to collect benefits. Duleep (1994) describes the state of the literature on how emigration affects the U.S. social security system as a "coarsely woven net of various strands of research, audacious assumptions, and rough approximations" (p. 31).…”
Section: Introductionmentioning
confidence: 99%